STUDY CHEMISTRY ANO PHITOCHEMISTRY OF TAGETES ELIPT/CA "CHINCHO" Y CALATHEA LUTEA "BIJAO" AS FUNCTIONAL FOODS - Tomás Ch, G. (2010)
We work with Tagetes etiptica "ch incho" of Huancayo y Catathea tutea "bijao" of Pucallpa. Oil obtained of "chincho" contained doubles bonds. "bijao· doesn't contain oil. The diclhorometane extrae! of "chincho" contains yelllow crystals TE1 and white powder TE2. The chromatographic analysis shows polar metabolites in both samples. Using phitochemist analysis we found, esteroidal triterpenoids, flavonoids, tanines, quinonas, antocianinas and alcaloides in te "chincho", In tehe "bijao" sample we found saponinas, gálic tanines, flavonoids, cumarines and alkaloids. In both sample we found calcium, phosphates, magnesium, iron, cinc, sulphur and potassium.